2020
DOI: 10.3390/cells9051107
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Acts as a Selective Glucocorticoid Receptor Agonist with Anti-Inflammatory Action without Affecting Tissue Regeneration in Zebrafish Larvae

Abstract: Glucocorticoids are effective anti-inflammatory drugs, but their clinical use is complicated due to the wide range of side effects they induce. Patients requiring glucocorticoid therapy would benefit from more selective glucocorticoid receptor (GR) agonists, capable of attenuating the immune response without causing these side effects. Ginsenosides, such as the compound Rg1, are natural plant compounds with structural similarity to classical glucocorticoids and well-documented anti-inflammatory effects. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…In a previous study, we demonstrated the conserved role of tlr2 in zebrafish as a PRR to recognize the mammalian TLR2 ligand Pam3CSK4, and identified a set of genes that are specifically expressed by activation of the downstream pathway of zebrafish tlr2 ( Yang et al, 2015 ). Moreover, He et al (2020) confirmed that tlr2 gene expression can be upregulated upon wounding in zebrafish larvae which is consistent with previous studies in mice. In addition, the study of Sommer et al (2020a) suggests that myd88 is required for induction of chemokine gene expression, such as ccl2 and cxcl11aa , following tail wounding.…”
Section: Introductionsupporting
confidence: 92%
“…In a previous study, we demonstrated the conserved role of tlr2 in zebrafish as a PRR to recognize the mammalian TLR2 ligand Pam3CSK4, and identified a set of genes that are specifically expressed by activation of the downstream pathway of zebrafish tlr2 ( Yang et al, 2015 ). Moreover, He et al (2020) confirmed that tlr2 gene expression can be upregulated upon wounding in zebrafish larvae which is consistent with previous studies in mice. In addition, the study of Sommer et al (2020a) suggests that myd88 is required for induction of chemokine gene expression, such as ccl2 and cxcl11aa , following tail wounding.…”
Section: Introductionsupporting
confidence: 92%
“…Interestingly, the ginsenoside Rg1 was shown to inhibit neutrophil migration in a Gr-dependent manner, but did not show any effect on tissue regeneration. These data suggest that this compound may be provide an interesting lead for the development of novel anti-inflammatory drugs with reduced side effects (He et al, 2020 ).…”
Section: The Use Of Zebrafish Inflammation Models For Research On Glumentioning
confidence: 97%
“…Various natural products have been demonstrated to have an inhibitory effect on the infiltration of leukocytes near the wounded area, including extracts from the medicinal herb ginseng (roots of plants in the genus Panax, such as Panax ginseng ) (Sun et al, 2019 ). One of the bioactive compounds in these extracts was shown to be the ginsenoside Rg1, a glycosylated steroid that exerts its anti-inflammatory activity through the glucocorticoid receptor (GR) (He et al, 2020 ). Using a library of fungal extracts, two compounds, sterigmatocystin and the antibiotic PF1052, were found to inhibit neutrophil recruitment (Wang et al, 2014 ).…”
Section: Inflammatory Disease Models In Zebrafishmentioning
confidence: 99%
“…A recent study proved the anti-inflammatory effect without tissue regeneration of Ginsenoside Rg1 on the zebrafish model [78]. These results are related to the selective GR agonist action of Ginsenoside Rg1 [78].…”
Section: Ginsenoside Rg1mentioning
confidence: 91%
“…Ginsenoside Rg1 demonstrated a better therapeutic index in inhibition of acute and chronic inflammation without causing hyperglycemia or osteoporosis as seen with dexamethasone [77]. A recent study proved the anti-inflammatory effect without tissue regeneration of Ginsenoside Rg1 on the zebrafish model [78]. These results are related to the selective GR agonist action of Ginsenoside Rg1 [78].…”
Section: Ginsenoside Rg1mentioning
confidence: 95%